The Effect of Sexual Education with the Plissit Method on Sexual Function Disorders in Type 2 DM Patients at the Limboto Health Center - Yunisa Bakari; Ita Sulistiani; Nirwanto K. Rahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Diabetes Mellitus is a chronic disease that is progressive and has a serious impact on the body's metabolic system. The PLISSIT model stands for four levels of intervention, namely Permission, Limited Information, Specific Suggestions, and Intensive Therapy. This study aims to determine the effect of sexual education with the PLISSIT method in reducing sexual function disorders in type 2 DM patients at the Limboto Health Center. The research method is using a quasi-experimental approach. The design used is a one group pretest-posttest design. The sample was taken using a non-probability sampling technique with a purposive sampling technique from a total population of 398 respondents to 44 respondents. The research instrument using Sexual Education with the PLISSIT Method was carried out according to SOP procedures and used IIEF and FSFI Questionnaires to measure the level of sexual disorders in men and women. The results showed that there was a statistically significant difference between the Pre FSFI and Post FSFI scores with a Z value of -5.061 and a significance value (p-value) of 0.000. Because the p value < 0.05, the Pre IIEF and Post IIEF p values are .000, where p < ? (0.05) is obtained, so it is concluded that H1 is accepted, meaning that there is an Effect of Sexual Education with the PLISSIT Method on Sexual Function Disorders in Type 2 Diabetes Mellitus Patients at Limboto Health Center. This research is expected to integrate sexual education of the PLISSIT method in the routine services of type 2 DM patients, especially in health education sessions and chronic disease clinics.